Report on integrating WEF Nexus into teaching and learning and on the outcome of the short training programme - Tsvuura, Susan; Senzanje, A.; Mudhara, M.; Mabhaudhi, Tafadzwanashe (CGIAR Initiative on NEXUS Gains, 2022)
This is a report on the survey of WEF Nexus teaching in selected higher education and tertiary institutions in South Africa, outcomes of the WEF Nexus short training programmes, and the development of WEF Nexus teaching material. The report presents the survey results on WEF Nexus teaching in South African higher and tertiary education institutions. The main findings of the survey are that; there is general knowledge of the WEF Nexus in the country, some of the institutions have been involved in WEF Nexus 'training' for a while now, WEF Nexus activities are found mainly in water-related departments at most institutions, WEF Nexus related work is mainly embedded in MSc and PhD research programmes, the WEF Nexus covered are wide but focused mainly on concepts, frameworks and application of models and tools. Most believed WEF Nexus should be focused on postgraduate students, and their institutions would welcome WEF Nexus-related teaching and learning. The deliverable also reports two WEF Nexus short course training undertaken in 2021 and 2022, initially virtually (due to Covid-19 restrictions) and then in person in 2022. The short courses were very well received, attracting more than 80 participants worldwide for the virtual versions and some 50 students for the in-person training. Details of the course contents of the training are presented in the report.